MECHANISMS FOR FORMING CAREER CHOICE MOTIVATION AMONG GRADUATING CLASS STUDENTS - Sanobar Khatamboyevna Asilova (Bright Mind Publishing, 2025)
This article discusses the pedagogical, psychological, and social factors influencing the formation of career choice motivation among graduating class students. It presents ideas and considerations about the necessary pedagogical mechanisms, methods, and tools for strengthening professional motivation.
Keywords: Career choice, motivation, graduating class students, career guidance, pedagogical mechanisms, psychological approach, professional motivation, cooperation between family and school, learner-centered education.